Remote instrumentation services on the e-infrastructure applications and tools - Davoli, Franco; SpringerLink (Online service). (Boston Springer, 2011)
This book focuses on all aspects related to the effective exploitation of remote instrumentation and to the building of complex virtual laboratories on top of real devices and infrastructures. These include service oriented architecture (SOA) and related middleware, high-speed networking in support of Grid applications, wireless Grids for acquisition devices and sensor networks, Quality Service (QoS) provisioning for real-time control, measurement instrumentation and methodology, as well as metrology issues in distributed systems.
Preface; Contents; Contributors; Part I Remote Instrumentation Services; Design and Evaluation of a RESTful API for ControllingINTbreak; and Monitoring Heterogeneous Devices; References; Parametric Jobs -- Facilitation of Instrument Elements UsageINTbreak; In Grid Applications; References; The Grid as a Software Application Provider in a Synchrotron Radiation Facility; References; Part II Support of Grid Functionalities; An Optimized Architecture for Supporting Data StreamingINTbreak; in Interactive Grids; References; EDGeS Bridge Technologies to Interconnect ServiceINTbreak
Electronic reproduction.
Keywords: Computational grids (Computer systems).; Computer networks -- Remote access; Electronic books